Well-Being Inequality in Europe - Botelho, Maria do Carmo (2018)
This paper aims to study the consequences of social inequality in the well-being of Europeans. How individuals differ in well-being in the European space? Do categorical and distributive inequalities influence well-being? We explore the well-being inequalities in Europe building upon the OECD Framework for Measuring Well-Being and Progress. Taking European Social Survey as the main empirical source, the interplay between key distributional (education, income) and categorical (gender, social class) dimensions of social inequalities in well-being was studied, under two levels of analysis of the OECD European social space – transnational (across individuals) and national (across countries). Social inequalities on well-being scores and well-being profiles were identified. Higher education, higher income, and belonging to a more privileged social class positively influence well-being; men tend to present higher well-being than women. The four well-being profiles identified among Europeans were shown to be clearly structured by social inequalities, opposing higher- and lower- qualified socio-occupations, and males and females' life circumstances. At a country level, profiles are mostly defined in terms of volume of well-being, mainly expressing regional affiliations and asymmetries of class, income and education. The developed analysis confirms the existence of multidimensional intersections between categorical and distributive social inequalities and well-being.